Efficiency and Generator Loading Analysis in GT 22 Blok 2 Gas and Steam Power Plant PT. PLN NP - Seputra M, Alif (Energy Insights, 2025)
Sengkang PLTGU is operated by PT. PLN NP has a total capacity of 315 MW. An important component in the PLTGU system is the generator. A generator has many problems that arise, including generator efficiency problems. The research determines the generator efficiency value and then determines the loading by which the generator efficiency value increases. To find the efficiency value by making daily and monthly load curves using generator output power, generator input power, generator nameplate and generator power losses at 50%, 80% and 100% loading. This research took samples that lasted for 9 days of generator efficiency at each load and compared the calculation results with the actual generator. It was found that the difference between 50% loading experienced a decrease in efficiency of 1.3473%, 80% loading experienced an increase of 1.96%, 100% loading experienced an increase of 1.09%. During the research the generator experienced reverse power so that the generator efficiency decreased. The average efficiency for 9 days was 97.2342%, with an average load of 25.2809 MW and an average input power of 26.1207 MW. In the manual book for Block 2 PLTGU PT. PLN NP generator efficiency value is divided by design into 3 loadings. Loading 50% efficiency is 95.7925%, loading 80% efficiency is 97.3377%, loading 100% efficiency is 97.9328%. So that the optimum generator efficiency is obtained at a load of 40.5544 MW (100% loading) with a value of 97.9328%.